Intertextualität bei Michael Ende, Cornelia Funke und Walter Moers - Gabrič, Ajda (Vestnik za tuje jezike, 2016)
This paper discusses intertextual phenomena in the novels The Neverending Story, Inkheart, and The City of Dreaming Books. Quotations and references in the novels are analysed as well as their functions, which range from showing the literary world as a net of quotations, characterisations of personas, and developing a sense of humour in young readers.
Keywords: Ende, Michael, 1929-1995; "Neskončna zgodba"; Literarne študije; Funke, Cornelia, 1958-; "Srce iz črnila"; Moers, Walter, 1957-; "Mesto sanjajočih knjig"; German-language literature; nemška književnost; young adult literature; mladinska književnost; medbesedilnost; postmodernizem; citiranje